On The Attitude оf the Church to Science (From the History of Atheistic Thought in Lithuania in the Late 19th and the Early 20th Centuries) - Barzdaitis, Juozas (Problemos, 1968)
Views of Lithuanian atheists of the end of the 19th and of the beginning of the 20th centuries on the attitude of the medieval church to science are investigated in the article. Lithuanian atheists referring to numerous facts depicted the struggle of the church against science and education. Their standpoints were wrong since they claimed that the church determined the position of science in medieval society, that discrepancy between new scientific data and principles of the Bible, the mercenary spirit of priests determined the medieval views on science.